Constructing an indigenous ecological curriculum: educational practices of the Sedulur Sikep community - Ningrum, Dwi Ayu; Budiyono, Budiyono; Utanto, Yuli (Indonesian Journal of Curriculum and Educational Technology Studies, 2025)
This study examines how Sedulur Sikep Community (Samin) in Pati, as one of the indigenous community units that still adheres to their principle of not sending their children to formal schools, designs, implements, and develops an ecological education curriculum. The approach used in this research is qualitative, which focuses on the hermeneutic phenomenology method to analyse the position of their ecological education curriculum from the perspective of social reconstruction. Data in this study were obtained by utilising the observation method and informal in-depth interviews. The discussion of the research findings centres around two major issues: First, since 2006, the development of the ecological education curriculum of Sedulur Sikep Community in Pati has been an effort in response to the cement factory establishment plan that threatens their lives and livelihoods as peasants. Second, in addition to the threat of ecological damage, the Sedulur Sikep Community is also dealing with the challenges of peasant regeneration, both within and outside the community, where peasants are ageing and the younger generation is reluctant to inherit their parents’ way of life as peasants. This study offers a new insight by explaining the phenomenon of the indigenous community from the perspective of curriculum studies. Eventually, this article implies the need for Indonesia's national curriculum to address future ecological problems, besides the national and global food security challenges.